Italijansko nasilje na območju Bloške planote, 1941–1943 - Mirjam Dujo Jurjevčič (Dileme)
The paper discusses the time of the Italian occupation (April 1941– September 1943) on the Bloke Plateau, i.e. the former and contemporary Municipality of Bloke. In April 1941, the Bloke Plateau was occupied by Italian forces, who caused the highest number of deaths during the Second World War in the area in question, i.e. 23% of all casualties, most of which were civilians. The paper presents specific examples of violence and deaths caused by the Italian army. The most extreme violence took place during the Italian offensive in July and August 1942, when there were mass shootings, the population was exiled to internment, and property was burned and looted. There is also a brief presentation of theemergence and activity of Village Guards in Bloke under Italian command.